Short-Term Audiological Results of Diode Laser in Comparison with Manual Perforation in Stapes Surgery - Hamerschmidt, Rogerio; Saab, Stephanie Sbizera; Carvalho, Bettina; Carmo, Carolina do (International Archives of Otorhinolaryngology, 2018)
Introduction Diode laser is a new alternative in stapes surgery for otosclerosis. The present study is the first to compare the short-term results of the surgery performed using diode laser to those obtained through the conventional fenestration technique.Objective To use audiometry to establish a comparative analysis between the functional results obtained through surgery for otosclerosis using diode laser and the conventional technique.Method Audiometric evaluation of 12 patients submitted to stapes surgery for otosclerosis, using diode laser or conventional fenestration by needle and drills, between 2014 and 2015. Each group was composed of 6 patients. Pre and post-operative measures were compared for three months in both groups. The speech recognition threshold, the air and bone conduction threshold, as well as the gap between them at 500 Hz, 1 KHz, 2 KHz and 4 KHz were measured.Results Significant difference in bone conduction and SRT was observed when compared post- and preoperative results in the diode group. However diode and conventional technique groups presented significant differences in air conduction and air-bone gap, suggesting that both can provide functional improvement.Conclusion Laser stapedotomy is a safe technique with good results. Both laser surgery and the conventional technique have improved the hearing of patients with a discreet advantage for the diode laser. Further prospective and randomized clinical trials are required to disclose all possible benefits of the stapes surgery using diode laser.
Keywords: otosclerosis; stapes surgery; diode laser